Stabilité politique et crise de la représentation au Chili - Georges Couffignal (Cahiers des Amériques Latines, 2011)
Chile has often been praised for its political stability. Two coalitions structure the party system and have governed for two decades: the centre left Concertation (PS, DC, PPD) had been the ruling party from 1990 to 2010, the other right wing coalition (UDI and RN) have been governing since. This situation results largely from a peculiar electoral system, a "binominal system", which guarantees each coalition roughly the same number of seats in the Parliament. But if this system assured a good governance during the long period of transition, it is going through a deep crisis today, as illustrated by the disaffection of the youth or the numerous labor disputes. The government parties seem incapable to meet requests which upset radically their traditional patterns. They will not be able to postpone any longer the reform of (the) electoral law.